A GFSK demodulator for low-IF Bluetooth receiver. - Bo Xia
An efficient mixed-mode Gaussian frequency-shift keying (GFSK) demodulator with a frequency offset cancellation circuit is presented. The structure is suitable for a low-IF Bluetooth receiver and can also be applied to other receivers involving continuous phase shift keying (CPSK) signals. The demodulator implementation is robust to tolerate process variations without requiring calibration. It can also track and cancel the time-varying local oscillator frequency offset between transmitter and receiver during the entire reception period. The chip was fabricated in CMOS 0.35-μm digital process; it consumes 3 mA from a 3-V power supply and occupies 0.7 mm2 of silicon area. A 16.2-dB input signal-to-noise ratio is obtained to achieve 0.1% bit-error rate as specified in Bluetooth specs. The co-channel interference rejection ratio is about 11 dB. Theoretical and experimental results are in good agreement.
Keywords: 0.35 micron; 16.2 dB; 3 V; 3 mA; CMOS digital process; CPSK signals; DC offset cancellation; Gaussian frequency-shift keying; Continuous phase shift keying signals; Frequency offset cancellation circuit; Low-IF Bluetooth receiver; Mixed-mode GFSK demodulator